Efficacy of Bonfils fiberoptic stylet for difficult tracheal intubation with double lumen tube: A prospective observational study. (December 2022) - Falcetta, Stefano; Bartolini, Federica; Carsetti, Andrea; Sorbello, Massimiliano; Gentili, Paolo; Coltrinari, Rosanna; Cortese, Gerardo; Godoroja, Daniela; Refai, Majed; Donati, Abele
Highlights: Positioning Double Lumen Tube is crucial to optimize one lung ventilation. Difficulties in positioning a DLT with direct laryngoscopy is higher compared to a single lumen tube. Bonfils rigid endoscope could be a safe and efficient rescue device for DLT positioning in case of direct laryngoscopy failure.